DEVELOPING A SUSTAINABLE EMPLOYEE PERFORMANCE MODEL THROUGH ENTREPRENEURIAL LEADERSHIP AND DIGITALIZATION: THE MEDIATING ROLE OF WORK MOTIVATION - Haekal, Muhammad; Lubis, Tona Aurora; Fitriaty (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
The purpose of this study is to analyze the influence of entrepreneurial leadership and digitalization on work motivation and sustainable employee performance, and to explore the mediating role of work motivation in the relationship between entrepreneurial leadership and digitalization on sustainable employee performance. This study uses a quantitative approach with a survey method by distributing questionnaires to 98 respondents in the Head Administration Bureau of the Jambi Provincial Secretariat. The collected data will be analyzed using the Partial Least Square (PLS) method with the help of SmartPLS software. Based on the results of the study, it can be concluded that Entrepreneurial Leadership, Digitalization, and Work Motivation in the Head Administration Bureau of the Jambi Provincial Secretariat are generally in the very good category, while sustainable employee performance is in the good category with a positive tendency. Although entrepreneurial leadership does not directly have a significant effect on sustainable employee performance, this variable is proven to have a positive and significant effect on work motivation, which in turn is able to improve employee performance sustainably. Meanwhile, digitalization is proven to have a positive and significant influence both directly and indirectly on sustainable employee performance, as well as significantly increasing employee work motivation. Furthermore, work motivation plays an important role as a mediating variable that strengthens the influence of entrepreneurial leadership and digitalization on sustainable employee performance, so that increasing work motivation becomes a strategic key in encouraging sustainable employee performance at the Leadership Administration Bureau of the Jambi Provincial Secretariat.